Maca Root (Lepidium meyenii) Extract Increases the Expression of MMP-1 and Stimulates Migration of Triple-Negative Breast Cancer Cells - Bizinelli, Daniela; Flores Navarro, Fernanda; Lima Costa Faldoni, Flavia [UNESP] (Taylor & Francis, 2021)
Maca root (Lepidium meyenii) extract is a worldwide consumed food supplement for sexual dysfunctions, increasing sperm production and its motility, and alleviating menopausal symptoms. Once maca root has a role in cell proliferation and motility, and its consumption may increase along with age, mainly in menopausal women, we aimed to investigate the plant effects on triple-negative breast cancer (TNBC) cell lines. Standardized maca root powdered extract showed significant cytotoxic activity in both MDA-MB-231 and Hs578T cells, and the IC50s were 2000 μg/ml and 3000 μg/ml, respectively. Both cell lines showed an increase in migratory capacity. Using bioinformatics tools, we established genes involved in the metastatic process, CAV1, LAMA4, and MMP-1, and the mRNAs expression was assessed by qPCR. Comparing the treated cells to the negative control, CAV1 presented a decreased expression by 2-fold in MDA-MB-231. LAMA4 presented a decrease by 4-fold in Hs578T cells. MMP-1 showed substantially increase mRNA expression in MDA-MB-231 by 86-fold and in Hs578T by 5-fold. To the best of our knowledge, this is the first study indicating that the human consumption of maca may be dangerous due to the upregulation in MMP-1 expression and the increase in TNBC migrated cells.